2020
DOI: 10.1051/bioconf/20201700045
|View full text |Cite
|
Sign up to set email alerts
|

Quality and consumer properties of bread baked from mixture of rye and wheat flour using iodine-containing additives

Abstract: Nowadays the state policy in the field of healthy nutrition of the population pays special attention to the development, production and sale of functional products with the purpose of preservation and promotion of health of the population, prevention of diseases, including those caused by defective and unbalanced nutrition of children and adults. The enrichment of bread with iodine is effective and safe, technologically feasible, has a minimal impact on the price of products. The bread production according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Currently, the state policy in the field of healthy nutrition of the population pays special attention to the development, production and sale of functional products in order to preserve and improve the health of the population, prevent diseases, including those caused by inadequate and unbalanced nutrition of children and adults [2].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the state policy in the field of healthy nutrition of the population pays special attention to the development, production and sale of functional products in order to preserve and improve the health of the population, prevent diseases, including those caused by inadequate and unbalanced nutrition of children and adults [2].…”
Section: Introductionmentioning
confidence: 99%
“…Kaliy yodid bilan boyitilgan un mahsulotlari tehnik ishlov berilganda, uning tarkibidagi pishirilgan non tarkibidagi yodning miqdori keski kamayib ketmasligi aniqlangan [14]. hubhasiz, yodning eng boy tabiiy oziq-ovqat manbalari dengiz baliqlari 0,39 6,9 mg/gekanligi aniqlandi.Bundan tashqari, sut va sut mahsulotlari va tuxumlarda 0,15-2,1 mg / g Journal of Chemistry of Goods and Traditional Medicine, Vol.…”
unclassified
“…1 During the technical processing of flour products enriched with potassium iodide, it was found that the iodine content in it is sharply reduced. It has been found that if iodcasein is added to wheat flour, the amount of iodine in bread baked from flour does not decrease dramatically [14].…”
mentioning
confidence: 99%